"I Didn't Meet My Mother; I Saw My Mother": The Challenges Facing Long-Term Care Residents and Their Families in the Age of COVID-19. (January 2022) - Avidor, Sharon; Ayalon, Liat
The present research examines the effects of protective measures due to the coronavirus disease 2019 (COVID-19) pandemic within long-term care (LTC) settings on residents and their family members. Open-ended qualitative interviews were conducted with 14 family members of older adults who resided in LTC settings during the first wave of the pandemic in Israel. The first theme identified is Rupture, including the physical disconnect; the disruption in routine treatment to residents; and decline in the satisfaction with the setting. The second theme is Response, including sharing viewpoints and involvement in decision-making, as well as an intense ambivalence shared by family members. Our findings highlight the distress caused to residents and family members by the isolation and restrictions in LTC settings during the pandemic and underscore values and priorities that are central to them and their family members, including maintaining continuity, transparency, and working in unison with their families, staff, and management.